A historical review of promotions of physical activity for adolescents in China from 1949 to 2020 - Gao, Guocheng; Liu, Jingxuan; Xu, Mingyue; Xia, Rui; Zhao, Lunan (Frontiers in Public Health, 2024)
Promotions of physical exercise for adolescents have become key elements of the country’s national sports and health campaigns in China. Specifically, these promotions have gone through four stages including Initial Institutionalization, Standardization and Legalization, Solidification and Publicization, and Comprehensiveness and Diversification, which are interpreted based on the Multiple Streams Framework with discussions of the role and dynamism of the problem streams, political streams, and policy streams included. The results reveal that the political streams, reified by the will of the governing party and the central government in particular, play a leading role in policy transformations. Consequently, identifications of existing problems and subsequent adoption of proper measures emerge as the key to generating policy developments in the promotion of physical exercise for adolescents in China.